Apospory and Diplospory in Diploid Boechera (Brassicaceae) May Facilitate Speciation by Recombination-Driven Apomixis-to-Sex Reversals - Carman, John G.; Mateo de Arias, Mayelyn; Gao, Lei; Zhao, Xinghua; Kowallis, Becky M.; Sherwood, David A.; Srivastava, Manoj K.; Dwivedi, Krishna K.; Price, Bo J.; Watts, Landon; Windham, Michael D. (Frontiers in Plant Science, 2019)
Apomixis (asexual seed formation) in angiosperms occurs either sporophytically, through adventitious embryony, or gametophytically, where an unreduced female gametophyte (embryo sac) forms and produces an unreduced egg that develops into an embryo parthenogenetically. Multiple types of gametophytic apomixis occur, and these are differentiated based on where and when the unreduced gametophyte forms, a process referred to as apomeiosis. Apomeiotic gametophytes form directly from ameiotic megasporocytes, as in Antennaria-type diplospory, from unreduced spores derived from 1st division meiotic restitutions, as in Taraxacum-type diplospory, or from cells of the ovule wall, as in Hieracium-type apospory. Multiple types of apomeiosis occasionally occur in the same plant, which suggests that the different types occur in response to temporal and/or spatial shifts in termination of sexual processes and onset timing of apomeiosis processes. To better understand the origins and evolutionary implications of apomixis in Boechera (Brassicaceae), we determined apomeiosis type for 64 accessions representing 44 taxonomic units. Plants expressing apospory and diplospory were equally common, and these generally produced reduced and unreduced pollen, respectively. Apospory and diplospory occurred simultaneously in individual plants of seven taxa. In Boechera, apomixis perpetuates otherwise sterile or semisterile interspecific hybrids (allodiploids) through multiple generations. Accordingly, ample time, in these multigenerational clones, is available for rare meioses to produce haploid, intergenomically recombined male and female gametes. The fusion of such gametes could then produce segmentally autoploidized progeny. If sex re-emerges among such progeny, then new and genomically unique sexual species could evolve. Herein, we present evidence that such apomixis-facilitated speciation is occurring in Boechera, and we hypothesize that it might also be occurring in facultatively apomictic allodiploids of other angiospermous taxa.